Efek Active Stretching Otot Plntar Flexor Ankle Terhadap Penurunan Nyeri Fasciitis Plantaris - HENDARTO, DONNY; , Totok Budi Santoso , S.Fis , MPH; , Agus Widodo, S.Fis., M.Fis (2015)
Background: plantar fasciitis is an inflammation of the plantar fascia. Factors that cause this plantar fasciitis are age, weight, activity, and trauma. The initial symptoms are experienced the onset of pain in the back of the heel. Active stretching of the plantar flexor muscles of the ankle is one of exercise methods therapy that can be applied to reduce the pain of plantar fasciitis. Objective: This study was aimed to determine the effects of the active stretching of the ankle plantar flexor muscles to reduce plantar fasciitis pain. Methods: This study applied a pre-experimental design by using one group pre test and post test design, the sample size are 18 people. The sample was determined by using purposive sampling of judgment sampling. Judgmental sampling is a non-probability sampling technique where the researcher selects units to be sampled based on their knowledge and professional judgment. Results: The data obtained are not normally distributed, statistical test of Wilcoxon test for the hypotheses, obtained value of p = 0.001 or p <0.05, means that there is a significant effects of active stretching of ankle plantar flexor muscles toward fasciitis pain reduction. Conclusion: active stretching of the ankle plantar flexor muscles has show significant effect toward the fasciitis pain reduction. Keywords: plantar fasciitis pain, active stretching, ankle plantar flexor